Intensity and Infestation Degree of Ectoparasite on White Leg Shrimp (Litopenaeus vannamei) Cultivated in Intensive Ponds - Yusma Latifatul Ummah; Gunanti mahasri; Laksmi Sulmartiwi (Airlangga University, 2024)
White leg shrimp (Litopenaeus vannamei) is a widely cultivated commodity in Indonesia. The high demand of white leg shrimp requires increased production. High stocking density in intensive cultivation and excessive amounts of feed are obstacles in white leg shrimp productiom. It will cause the shrimp to become stressed and susceptible to pathogen attack , one of them is ectoparasite. This research was conducted from August to September 2023 with the aim of determining the intensity and infestation degree of ectoparasite on white leg shrimp that cultivated in intensive ponds. The samples of white leg shrimp in this study were 50 individuals by purposive random sampling method. Observations were carried out by natif method in the Cultivation and Anatomy Laboratory, Faculty of Fisheries and Marine, Airlangga University. The results showed that white leg shrimp cultivated in intensive ponds were infested by Zoothamnium sp. with intensity 184 individuals/head, Vorticella sp. with intensity 268 individuals/head and Epistylis sp. with intensity 235 individuals/head. Each ectoparasite has a very severe infestation degree